2011
DOI: 10.4061/2011/503293
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of CSF Tau and Aβ42 in Dementia: A Meta‐Analysis

Abstract: CSF tau and Aβ42 are considered as important markers to diagnose Alzheimer's disease in early stages. Hence, it is important to assess their status in different types of dementia. The main objective of this study was to assess whether these CSF biomarkers can be used to make the differential diagnosis of AD. In the present study, articles published from 1998 till 2009 were taken and meta-analysis was performed to clarify the consistency in trends of biomarkers- CSF tau and Aβ 42 in AD and other dementias and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
(99 reference statements)
2
12
0
Order By: Relevance
“…Because concurrent presence of fibrillar Aβ deposits occurs in the majority of patients with DLB, it is possible that the reduced Aβ 1 – 42 levels in the CSF have also been documented in patients with other dementia [ 4 ]. However, meta-analytic study indicates that CSF Aβ 1–42 can serve as a diagnostic and surrogate biomarker for Aβ deposition in the brain [ 26 ]. Second, the ranges of Aβ 1–42 levels partially overlap between AD and a-MCI, and it is therefore not possible to establish a cut-off value that discriminates between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Because concurrent presence of fibrillar Aβ deposits occurs in the majority of patients with DLB, it is possible that the reduced Aβ 1 – 42 levels in the CSF have also been documented in patients with other dementia [ 4 ]. However, meta-analytic study indicates that CSF Aβ 1–42 can serve as a diagnostic and surrogate biomarker for Aβ deposition in the brain [ 26 ]. Second, the ranges of Aβ 1–42 levels partially overlap between AD and a-MCI, and it is therefore not possible to establish a cut-off value that discriminates between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, low CSF levels of Aβ1-42 and high CSF levels of P-tau, as well as positive CNS images of amyloid deposits accurately predicted development of mild cognitive impairment (MCI) and probable AD [10, 11]. However, there was substantial overlap in these biomarkers between patients who subsequently developed AD and those who later manifested other forms of dementia or no signs of dementia, even when concentrations of these CSF proteins were considered together or as ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The most consistent AD biomarkers have been identified in cerebrospinal fluid (CSF) [4] , [5] , [6] , [7] . CSF biomarkers in combination with recently improved neuroimaging have increased the rate of early diagnosis of preclinical AD patients, but CSF studies require invasive sample collection [8] , [9] , [10] , [11] , [12] , [13] , [14] . Studies have shown overlap in CSF biomarkers among MCI patients who later manifest AD, those who develop non-AD forms of dementia, and those who never exhibit signs of dementia [8] , [9] , [10] , [11] , [12] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%
“…CSF biomarkers in combination with recently improved neuroimaging have increased the rate of early diagnosis of preclinical AD patients, but CSF studies require invasive sample collection [8] , [9] , [10] , [11] , [12] , [13] , [14] . Studies have shown overlap in CSF biomarkers among MCI patients who later manifest AD, those who develop non-AD forms of dementia, and those who never exhibit signs of dementia [8] , [9] , [10] , [11] , [12] , [13] , [14] . The presence of nonspecific binding of imaging radiotracers in AD cases, especially those for phosphorylated tau (P-tau), may limit their utility as accurate and predictive biomarker tools for diagnosis of preclinical AD [15] .…”
Section: Introductionmentioning
confidence: 99%